'Bicycle-Face' and 'Lawn Tennis' Girls: Debating girls' health in late nineteenth- and early twentieth-century British periodicals. Issue 1 (2nd January 2019) - Marland, Hilary
Abstract : In the final quarter of the nineteenth century, as periodical literature itself diversified and increased in volume, a growing amount of copy was devoted to the medical issues of the day, including debates about the limits of young women's energy and the impact of the extension of their activities in education, public life and sport on their health and vitality, and their future role as mothers. The article explores the ways in which doctors in particular utilized these outlets to convey their opinions and concerns, revealing a great diversity of viewpoints as well as the flexible editorial policies of many of these journals. Both male and a growing cohort of female doctors employed the platform of the periodical to popularize and make relevant medical ideas, while also building on, highlighting and creating broader cultural and gendered perspectives and emblems of girlhood.